smile asked in Science & MathematicsMathematics · 8 years ago

# math help ! solving elimination in non standard form!!?

9x - 3y = 63

7x - 3y = 45

Relevance
• ?
Lv 7
8 years ago

9x - 3y = 63

7x - 3y = 45.........Multiply by - 1

9x - 3y = 63

-7x + 3y = -45

2x = 18

x = 9

9(9) - 3y = 63

81 - 3y = 63

-81........- 81

- 3y = - 18

y = 6

( 9 , 6 ) ......................ANSWER

Let me know if you have questions on this or any other math problem

or would like a great math tutor.

Mathcerely,

Robert Jones.......Master in Mathematics (Un of Notre Dame)

"Teacher of Fine Students"

I tutor the struggling to improve grades and learning.

I tutor the very bright to make them faster, smarter, and

..........better looking like myself......Well first two are true.

If interested let me know how to get in touch. If not that is fine.

I tutor via skype.

• Anonymous
8 years ago

9x-3y=63

7x-3y=45

9x-3y=63

-7x=3y=-45

(-3y and +3y gets canceled and the rest we solve it)

it becomes:-

2x= 18

then,

x=18/2=9

therfore,

x=9

to find y(substitute the value of x in any one eq.)

7x-3y=45

7(9)-3y=45

63-3y=45

-3y=-18

y=6

therefore the value of:

x=9 , y=6

• Moon
Lv 7
8 years ago

9x - 3y = 63 ........eq1

7x - 3y = 45 .........eq2

-----------------------------

2x = 18 ..............eq1 - eq2

x = 9 ..................................... x solved

9x - 3y = 63 ........eq1

81 - 3y = 63

-3y = 63 - 81 = -18

y = 6 ....................................... y solved

check:

7x - 3y = 45 .........eq2

7*9 - 3*6 = 45

63 - 18 = 45 ........................ true!!!

(x,y) = (9, 6)

.......

• Como
Lv 7
8 years ago

9x - 3y = 63

-7x + 3y = - 45______ADD

2x = 18

x = 9

63 - 3y = 45

18 = 3y

y = 6

x = 9 , y = 6

• 8 years ago

-1 (9x-3y=63

7x-3y=45

-9x+3y=-63

7x-3y=45

--------------

-2x=-18

x=9 if x=9 y=6

• 8 years ago

9x - 3y = 63

7x - 3y = 45

------------------ (subtract)

2x = 18

x = 9

and if x =9, then 9(9) - 3y = 63

81 - 63 = 3y

18 = 3y

y = 6

(9 , 6) = (x , y)

check in the other equation:

7(9) - 3(6) = 63 - 18 = 45 checks

• 4 years ago

the 1st ingredient to do is to get the equations into familiar variety: 6x -6y = 6 -4x + 8y = 4 divide out the 6 from the 1st equation and divide the 2nd equation through four. you will then have: x - y = a million -x + 2y = a million upload the two equations. the x's cancel out and you have: 2y - y = 2 y = 2 exchange y=2 into the 1st equation to get x - 2 = a million x = 3